Target gene selectivity of hypoxia-inducible factor-α in renal cancer cells is conveyed by post-DNA-binding mechanisms - Lau, K W (Nature Publishing Group, 2007)
Inactivation of the von Hippel–Lindau tumour suppressor in renal cell carcinoma (RCC) leads to failure of proteolytic regulation of the α subunits of hypoxia-inducible factor (HIF), constitutive upregulation of the HIF complex, and overexpression of HIF target genes. However, recent studies have indicated that in this setting, upregulation of the closely related HIF-α isoforms, HIF-1α and HIF-2α, have contrasting effects on tumour growth, and activate distinct sets of target genes. To pursue these findings, we sought to elucidate the mechanisms underlying target gene selectivity for HIF-1α and HIF-2α. Using chromatin immunoprecipitation to probe binding to hypoxia response elements in vivo, and expression of chimaeric molecules bearing reciprocal domain exchanges between HIF-1α and HIF-2α molecules, we show that selective activation of HIF-α target gene expression is not dependent on selective DNA-binding at the target locus, but depends on non-equivalent C-terminal portions of these molecules. Our data indicate that post-DNA binding mechanisms that are dissimilar for HIF-1α and HIF-2α determine target gene selectivity in RCC cells.